2019
DOI: 10.1161/jaha.118.011598
|View full text |Cite
|
Sign up to set email alerts
|

Thirty‐Day Readmission After Infective Endocarditis: Analysis From a Nationwide Readmission Database

Abstract: Background The contemporary incidence of and reasons for early readmission after infective endocarditis ( IE ) are not well known. Therefore, we analyzed 30‐day readmission demographics after IE from the US Nationwide Readmission Database. Methods and Results We examined the 2010 to 2014 Nationwide Readmission Database to identify index admissions for a primary diagnosis of IE with survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 26 publications
10
23
1
Order By: Relevance
“…The percentage of positive blood culture and TTE pictures suggestive for IE, according to the Duke modified criteria, observed in our study is due to an earlier alert of an infectious disease consultant closely involved with the hospital team for the management of IE patients. In fact, in our patients, both blood culture and TTE were performed within the first days from admission to the emergency unit, confirming the utility of an early TTE [26,[28][29]. Fever was the main symptom of IE, highlighting that this symptom is vital for the suspicion of IE.…”
Section: Discussionsupporting
confidence: 72%
“…The percentage of positive blood culture and TTE pictures suggestive for IE, according to the Duke modified criteria, observed in our study is due to an earlier alert of an infectious disease consultant closely involved with the hospital team for the management of IE patients. In fact, in our patients, both blood culture and TTE were performed within the first days from admission to the emergency unit, confirming the utility of an early TTE [26,[28][29]. Fever was the main symptom of IE, highlighting that this symptom is vital for the suspicion of IE.…”
Section: Discussionsupporting
confidence: 72%
“…We received from the Spanish Ministry of Health the SNHDD including all patients with a primary (first position) or secondary diagnosis (positions 2 to 14) of IE (ICD-9-CM codes 421.0, 421.1, 421.9, 424.99) hospitalized from year 2001 to year 2015. These codes have been frequently used in previous studies of IE using hospital discharge databases [3, 4, 28, 33].…”
Section: Methodsmentioning
confidence: 99%
“…Predictors of increased risk for re-admission included female sex, staphylococcus aureus infection, diabetes mellitus, chronic obstructive pulmonary disease, chronic liver disease, acute kidney injury, acute heart failure and anemia. In addition to above, the duration of admission was also a risk factor for readmission in the study by Morita et al (2019). The incidence of Staphylococcus aureus IE been steadily rising, and currently Staphylococcus aureus is the leading cause of acute IE (Tong et al, 2015).…”
Section: Discussionmentioning
confidence: 79%
“…They found an 18% mortality rate (95% confidence interval (CI): 14%-23%) one-year post-discharge and 65% (95% CI: 59%-71%) re-admission rate within the first year. Table 2 lists all the studies found in English literature describing the readmission rates for IE (Amodeo et al, 2009;Kashef et al, 2017;Morita et al, 2019;Rasmussen et al, 2017). The study by Morita et al, also a population based study reported a readmission rate of 24.8% in 2010-2014 NRD database (Morita et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation